Coevolution of post‐Palaeozoic arthropod basibiont diversity and encrusting bryozoan epibiont diversity?. (8th August 2019) - Key, Marcus M.; Schweitzer, Carrie E.
Abstract : We hypothesize that the diversification of motile marine arthropods with hard carapaces resulted in a concurrent increase in the diversity of encrusting marine bryozoans whose larvae exploited those substrates through the Mesozoic and Cenozoic. To test this, family‐level data were tabulated from the literature on the post‐Palaeozoic diversity of motile marine arthropod basibionts and sessile marine bryozoan epibionts. We found strong temporal correlation from general to more specific basibiont‐epibiont relationships (i.e. arthropods and bryozoans in general to decapods and encrusting gymnolaemates to robust decapods and encrusting cheilostomes in particular). We compared the diversification of bryozoans to another common group of basibionts (i.e. molluscs) and found weaker correlations. This suggests that the diversification of motile arthropods with hard carapaces (e.g. brachyuran crabs) may have played a role in the diversification of sessile bryozoans (e.g. encrusting cheilostomes) in the post‐Palaeozoic.